HUBUNGANMUTU PELAYANAN BIDAN DENGAN KETERATURAN KUNJUNGAN ANC PADAIBU HAMIL TMIII - Shinta, Dyen Laras (JURNAL MEDIA KESEHATAN, 2016)
The main indicatorof health in a country is mortality of mother rate. About 20-30%of pregnancy have the risk for baby and mother. It shows less degradation, so the service ofchild and mother health have to be improved. Antenatal care (ANC) have to be improvedbecause it represent the midwife first step to detect early complication. The standard of ANCconsist of 6 standard in applying of 14T’s operational. The one of factors is influencingpregnant mother to do ANC are responsiveness, reability, asurance, emphaty and tangible.The purpose of this research to know the relation of midwife services quality with ANC’s visitregularity of TM III pregnant mother on Puskesmas Penurunan work area in Bengkulu city at2013. This research type is descriptive-analitic with cross sectional approached. The samplewhich used in this research are all TM III pregnant mother at January-April, there are 44people. This research is execute on 2013th 30 May-30 June, use quesioner as primary data.This research result there are most responder said the services quality are less and mostrespondent didn’t do ANC visit regulary and there is indicate relation have meaning bitweeenthe midwife service’s quality with the regularity of ANC’ s visit of TM III pregnant mother(p=0,008) on Puskesmas Penurunan work area on Bengkulu city at 2013. The expected of thisresearch could be used as input to the health’s officer which related to regularity ANC’s visitof TM III pregnant mothers and the midwife quality’s service on Puskesmas Penurunan workarea on Bengkulu city at 2013.